Effect of Extracts of Dialium guineense Stem Bark on Lipid Profile and CCl4- Induced Histological Changes in Liver of Wistar Rats - Abu O.D; Eromosele A.I; Osarhenomase E.G (International Journal of Lipids, 2022)
The present study investigated the effect of aqueous and ethanol extracts of Dialiumguineense stem bark on lipid profile and CCl4- induced histological changes in liver of Wistar rats. Adult male Wistar rats (n = 25) weighing 160 – 180 g (mean weight = 170 ± 10 g) were randomly assigned to five groups (5 rats per group): normal control, CCl4 control, silymarin, aqueous extract and ethanol extract groups. With the exception of normal control, the rats were exposed to CCl4 (single oral dose of 1.0 mL/kg body weight, bwt). Silymarin group rats were administered standard hepatoprotective drug, silymarin, at a dose of 100 mg/kg bwt, while those in the two treatment groups received 1000 mg/kg bwt of aqueous or ethanol extract orally for 28 days. Lipid profile parameters were determined in plasma, while rat liver was subjected to histopathological examination. The results showed that the levels of total cholesterol (TC), triacylglycerol (TG), high-density lipoprotein cholesterol (HDL-C), very-low density lipoprotein cholesterol (VLDL-C), low-density lipoprotein cholesterol (LDL-C) as well as atherogenic index of plasma (AIP) were significantly lower in CCl4 control group than in normal control group, but they were increased by extract treatment (p < 0.05). However, there were no significant differences in atherogenic coefficient (AC) and cardiac risk ratio (CRR) among the groups (p > 0.05). Carbon tetrachloride (CCl4) markedly disrupted the structure of hepatocytes and induced steatosis (intra-hepatocyte fat in-growth and inflammation) which was predominantly microvesicular. However, treatment with aqueous and ethanol extracts of D. guineense stem bark showed marked regeneration of hepatocytes (unremarkable hepatic lobular architecture). The toxic hepatic injury induced by CCl4 was significantly blocked by the plant extracts.
Keywords: Cholesterol